A highly selective colorimetric fluorescence probe for Cu2+ in aqueous media: the synthesis, DFT investigation and its application in living cells. Issue 7 (3rd February 2020) - Li, Dandan; Gong, Lihua; Qiao, Zhenyang; Zhu, Congcong; Jia, Qiaojuan; Kong, Huajie; Jiao, Shuyan
Abstract : A novel highly selective colorimetric fluorescence probe, POPH, has been successfully synthesized and it shows remarkable selective and sensitive response to Cu 2+ in aqueous media (HEPES buffer, pH = 7.4). Abstract : A novel highly selective colorimetric fluorescence probe, POPH, has been successfully synthesized and it shows remarkable selective and sensitive response to Cu 2+ in aqueous media (HEPES buffer, pH = 7.4). The fluorescence of probe POPH immediately decreased when 1.1 equiv. of Cu 2+ was added to a solution of probe POPH, accompanied by color change from wathet blue to colorless under 365 nm UV lamp illumination. The possible bonding model of probe POPH with Cu 2+ was examined through HRMS, FESEM, TEM, FTIR spectroscopy and DFT calculations. Moreover, the probe POPH could be used for monitoring Cu 2+ in living cells using laser scanning confocal microscopy.